Pengembangan E-Modul Interaktif Berbasis Android dengan Pendekatan Etnosains pada Upacara Adat Kenduri Sko di SMA - Ikhwal, Muhammad; Minarsih, Minarsih; Puspita, Sri Dewi; Alfaidzi, M Haykal; Afifah, Nisaul (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The purpose of this study was to develop an Android-based interactive e-module with an ethnoscience approach at the Kenduri Sko traditional ceremony for the high school level. The method in this research is qualitative based on ethnography with qualitative descriptive data collection using the Miles and Huberman model. Interviews were conducted on key informants, namely community leaders, depatis, and prostitutes who were considered capable of providing accurate information. Validation is carried out by material experts, media experts and student responses to the e-modules that have been made. The results of validation by validation by material experts are valid with the average score of all aspects is 3.56 with a very good category. Validation by media experts is valid and feasible to use with an average score of all aspects is 3.47 with a very good category. The validation of student responses is also valid or feasible to use with an average score of 3.38 in the very good category.